RICHARD POWERS’ THE OVERSTORY: THE INTERCONNECTEDNESS OF HUMAN LIVES AND TREES - Hameed, Delveen; Babo, Sherzad (Humanities Journal of University of Zakho, 2025)
The present article examines the deep connection that binds human beings and trees in Richard Powers’s The Overstory (2018). The study examines the relationships between nine characters and different kinds of ancient trees, exploring how these connections impact their lives and represent various facets of the human condition, using an ecocritical approach as a framework. Ecocriticism is the study of the relationship between human beings and nature in literary works. In addition, the novel’s sections- Roots, Trunk, Crown, and Seeds—are named after various components of a tree. Among the key characters in the novel are Patricia Westerford, Adam Appich, Mimi Ma, and Nicholas Hoel. The decisions, conducts, and actions of these characters are largely affected by the kind of trees they grow and take assiduous effort to propagate, such as chestnuts, mulberries, banyan trees, and maple trees. The characters’ interactions with trees trigger profound changes in their lives, causing them to reevaluate their relationship with the natural world. This paper concludes that trees are living entities that influence the characters’ identity, memory, and personal growth.